Development of an analytical method for the quantification of pfaffic acid in Brazilian ginseng (Hebanthe eriantha) - Rodrigues, Marili Villa Nova; de Paula Souza, Kelly; Rehder, Vera Lucia Garcia; Vilela, Gisele Freitas [UNESP]; Montanari Júnior, ílio; Figueira, Glyn Mara; Rath, Susanne (Elsevier, 2013)
Hebanthe eriantha (Poir.) Pedersen (Amaranthaceae), which is known as Brazilian ginseng is widely used in folk medicine as an aphrodisiac and antidiabetic tonic. The anti-tumor activity, attributed to the pfaffic acid present in roots of H. eriantha, is responsible for the great interest in the commercialization of this species. In Brazil, the species H. eriantha is mainly used in commercial preparations, although other plants of the genus Pfaffia and Hebanthe have been marketed as Pfaffia paniculata or Brazilian ginseng. The pfaffic acid present in the roots is mainly conjugated with sugars (pfaffosides) and can be used as an active marker of H. eriantha, which helps to differentiate this species from others marketed as Brazilian ginseng. The main objective of this study was to develop and validate a liquid chromatographic method to quantify pfaffic acid in the roots of H. eriantha. The extraction and hydrolysis conditions were optimized using an univariate and experimental design, respectively, and the quantification of pfaffic acid by high performance liquid chromatography with diode-array detection (HPLC-DAD) was validated. This method was used to evaluate the pfaffic acid content in 30 different genotypes of the species from a germplasm collection. The content of pfaffic acid ranged from 0.97 to 4.29% (w/w) on a dry weight basis. © 2013 Elsevier B.V.
Keywords: Amaranthaceae; Brazilian ginseng; Hebanthe eriantha; HPLC-DAD-MS; Pfaffic acid; antineoplastic agent; pfaffic acid; pfaffoside a; pfaffoside b; pfaffoside c; pfaffoside d; pfaffoside e; pfaffoside f; saponin derivative; sugar; triterpene; unclassified drug; analytic method; antineoplastic activity; dry weight; extraction; genotype; germplasm; ginseng; high performance liquid chromatography; high performance liquid chromatography with diode array detection; hydrolysis; nonhuman; plant root; priority journal; quality control